Efeito da estimulação elétrica de alta voltagem no processo inflamatório - Ortiz, Maria Cristina Sandoval (Universidade Federal de São Carlos, 2009)
Inflammation is the response of protection of the body to an aggression in order to obtain the healing. This process makes part of many diseases attended by physical therapist, however when it is increased, limits the fast recovery of the patient. High voltage pulsed current (HVPC) is one of the modalities used to interview of inflammatory process; the type of stimulation is considered monophasic pulsed that produces a high-driving voltage 150 V, but the total current (average) delivered to the tissue per second does not exceed 1.2 to 1.5mA. There are many studies that evaluate the effect of HVPC in swelling, but the major part was made in animal models and only one in human beings was found in the review of the literature. The results of the studies in animals had showed the effectiveness of HVPC in reduction of edema, but the study in human only showed clinical differences not statistically significant. Additionally, the action mechanism of HVPC is unknown and some hypotheses have been proposed for explaining its effect. The objective of this study was evaluate the effectiveness of HVPC in the inflammation process, both in humans and animals in a submotor level, 100pps of frequency and 45min of treatment. We made a controlled and randomized clinical trial in subjects with lateral sprain of ankle measuring pain, edema, range of mobility and some parameters of the gait comparing three groups: control group (CG) with standard physical therapy, HVPC(-) with standard physical therapy plus HVPC negative polarity and HVPC(+) with standard physical therapy plus HVPC positive polarity. There was not difference between the study groups, but the clinical results suggested that HVPC(-) could contribute to accelerate the recovery of inflammatory process. Second, an experimental study was done in animals evaluating pain, edema, serum histamine and albumin and the cartilage, comparing a control group, a inflammation group with HVPC(-), a inflammation group with HVPC placebo and the last group only with HVPC(-). We did not find differences between the groups in the variables, only observed the lowest cellularity in the cartilage of inflammation group+HVPC(-) and lowest optical density in inflammation group+HVPC placebo. These results are a contribution for the understanding of the biophysical agent used in the physical therapy, however is necessary more clinical studies including higher sample size, in order to demonstrate the effects of HVPC on the inflammation process.
Keywords: Eletroterapia; Estimulação elétrica; Edema; Inflamação; Entorse; Swelling; Inflammation; Electrical stimulation; Sprain; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL